2011
DOI: 10.1159/000326857
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome Associated with the Screening Interval for Gastric Cancer in Korea

Abstract: Background/Aims: Early gastric cancer (EGC) can be treated by endoscopic resection, which results in an excellent prognosis. Optimal screening intervals considering risk factors for gastric cancer have not been established. The aim of this study was to determine the maximum gastric cancer screening interval in terms of long-term survival. Methods: Curative resection was performed in 561 patients with gastric cancer who had completed a questionnaire on their previous history of screening tests and risk factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…An approach to risk stratification and thereby a stepwise increasing the frequency of screening endoscopy thus appears to be more suitable. Our data confirmed the effectiveness of periodic endoscopic screening within 2–3 years on improvement in the overall survival,19, 32 while annual endoscopic screening did not increase the GC‐related survival rates further in comparison with biennial screening. The reason could be attributable to the localized and regional diseases in most cases of both annual and biennial screening groups, which yielded an excellent disease‐free survival as well as overall survival following curative treatment not only by surgery but also by a less invasive endoscopic resection.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…An approach to risk stratification and thereby a stepwise increasing the frequency of screening endoscopy thus appears to be more suitable. Our data confirmed the effectiveness of periodic endoscopic screening within 2–3 years on improvement in the overall survival,19, 32 while annual endoscopic screening did not increase the GC‐related survival rates further in comparison with biennial screening. The reason could be attributable to the localized and regional diseases in most cases of both annual and biennial screening groups, which yielded an excellent disease‐free survival as well as overall survival following curative treatment not only by surgery but also by a less invasive endoscopic resection.…”
Section: Discussionsupporting
confidence: 82%
“…Although a debate over the cost and benefit of the screening is ongoing, interest has shifted to determining the preferred strategy and discerning the most effective ways of implementing screening in high‐incidence countries of GC 12, 17, 25. Most endoscopic screening studies have reported that 2‐ to 3‐year intervals are sufficient to detect early stage GC,11, 12, 19–21, 32 while 4‐ to 5‐year intervals did not affect the mortality in a high‐risk Chinese cohort 33. Our large proportion of EGC (90.7%) within 2 years after an earlier negative endoscopy is well within the upper range of preceding reports (87.2–96%) and reinforces current recommendations of a 2‐year interval for population‐based screening in high‐incidence countries 20, 21.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, H pylori is associated with both intestinal and diffuse types of GC, and through damage to epithelial cells, H pylori‐ associated chronic active gastritis is known to be a major risk factor for GC . Because the incidence of GC is high in patients diagnosed with IM, GC screening is recommended . In Korea, where the incidence of GC is the highest in the world, endoscopic screening for early GC is recommended every 2 years for adults over 40 years old.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16,20,2931] According to our results, stage-adjusted overall survival rates were not significantly different among the screening interval groups. Thus, these results may suggest that the survival benefit of screening endoscopy was achieved by the early detection of gastric cancer.…”
Section: Discussionmentioning
confidence: 62%